2020
DOI: 10.3390/en13010242
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Analysis of the Heat-to-Power Ratio from the Supply and Demand Sides of Cities in Northern China

Abstract: Combined heat and power (CHP), an efficient heating method with cascades use of energy, accounts for approximately 50% of the heat sources in northern China. Many researchers have made significant efforts to improve its energy efficiency and environmental effects with important achievements. Given that the system produces heat and electricity at the same time, this study focuses on the role of CHP in the holistic urban energy system and points out the mismatch between the demand and supply sides of urban energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…(1) The regional power-generation cost coefficient update rule (Yin et al, 2020). The cumulative power-generation cost coefficient of the regional energy Internet, according to Eq.…”
Section: Interaction Between the System Layer And Regional Layermentioning
confidence: 99%
“…(1) The regional power-generation cost coefficient update rule (Yin et al, 2020). The cumulative power-generation cost coefficient of the regional energy Internet, according to Eq.…”
Section: Interaction Between the System Layer And Regional Layermentioning
confidence: 99%
“…In addition, onsite electricity can be provided by reducing transmission losses. Finally, waste heat can also be exploited locally [8] and pollutant emissions significantly reduced by means of flue gas treatments [9].…”
Section: Problem Statementmentioning
confidence: 99%
“…Pareto analysis showed that planned maintenance and machine failure caused about 80% of total downtime [19]. In improving the productivity of the machine, the management of decision or maintenance policy must be appropriate [20]. By reviewing of 251 academic and professional papers regarding maintenance performance measurement, they mentioned that today the role of maintenance has shifted to the strategic business support from the production support in the organization.…”
Section: Introductionmentioning
confidence: 99%